2018
DOI: 10.1242/dev.158162
|View full text |Cite
|
Sign up to set email alerts
|

Runx1 is sufficient for blood cell formation from non-hemogenic endothelial cells in vivo only during early embryogenesis

Abstract: Hematopoietic cells differentiate during embryogenesis from a population of endothelial cells called hemogenic endothelium (HE) in a process called the endothelial-to-hematopoietic transition (EHT). The transcription factor Runx1 is required for EHT, but for how long and which endothelial cells are competent to respond to Runx1 are not known. Here, we show that the ability of Runx1 to induce EHT in non-hemogenic endothelial cells depends on the anatomical location of the cell and the developmental age of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Thus, perturbation of blood development at hemogenic sites can be caused by the selective effect of transcription factors on HE specification, EHT per se, or alternatively by their effect on amplification, survival, and specification of blood progenitors at the post-EHT stage. Among transcription factors involved in hematopoietic development, Runx1 has been shown to specify endothelial cells as hemogenic during a very short developmental window ( Yzaguirre et al., 2018 ). In addition, Runx1 affects post-EHT stages of blood development, including transition of VEC + CD45 − CD41 + type I HSCs to the CD45 + type II HSCs ( Liakhovitskaia et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, perturbation of blood development at hemogenic sites can be caused by the selective effect of transcription factors on HE specification, EHT per se, or alternatively by their effect on amplification, survival, and specification of blood progenitors at the post-EHT stage. Among transcription factors involved in hematopoietic development, Runx1 has been shown to specify endothelial cells as hemogenic during a very short developmental window ( Yzaguirre et al., 2018 ). In addition, Runx1 affects post-EHT stages of blood development, including transition of VEC + CD45 − CD41 + type I HSCs to the CD45 + type II HSCs ( Liakhovitskaia et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initial hematopoietic specification associated with upregulation of CD41 does not require Runx1 ( Liakhovitskaia et al., 2014 ). Runx1 sensitivity of the embryonic endothelium is limited to the period around E7.5–E8.5 ( Tanaka et al., 2012 , Yzaguirre et al., 2018 ). Induced stage-specific inactivation using explant cultures followed by long-term transplantations showed that, up to E11.5, Runx1 is absolutely required for HSC development but becomes dispensable after that ( Tober et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas vasculogenesis in mouse ES cells occurs within the first 9 days following removal of LIF from the cell culture medium, the differentiation of leukocytes occurs between Day 12 and Day 14 of cell culture, which implies that inhibition of vasculogenesis should abolish differentiation of leukocytic cells (Hannig et al, ). During embryogenesis, hematopoietic stem cells differentiate from a population of endothelial cells called hemogenic endothelium (HE) in a process called the endothelial‐to‐hematopoietic transition (EHT) and is regulated by the transcription factor Runx1 (Yzaguirre, Howell, Li, Liu, & Speck, ). Recently transcriptional overlap between hemogenic endothelial cells and hematopoietic progenitor cells was reported (Angelos, Abrahante, Blum, & Kaufman, ).…”
Section: Discussionmentioning
confidence: 99%